2022
DOI: 10.3390/metabo12030198
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State Fermented Okara with Aspergillus spp. Improves Lipid Metabolism and High-Fat Diet Induced Obesity

Abstract: Okara is a major by-product of soymilk and tofu production. Despite retaining abundant nutrients after the process, okara is often under-utilized. In this study, solid-state fermentation (SSF) of okara was carried out using a koji starter (containing both Aspergillus oryzae and Aspergillus sojae) with the intention of releasing its untapped nutrients. Its effects on lipid metabolism in diet-induced obesity (DIO) were observed. The nutritional profile of fermented okara was elucidated using the following parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 48 publications
0
1
0
Order By: Relevance
“…Okara has been reported to prevent excessive lipid absorption due to the high content of dietary fiber. 32,33 Furthermore, OPH supplementation for 4 weeks was not harmful to the serum markers of lipids (triglyceride and total cholesterol), glucose, liver (AST, ALT), kidney (uric acid and creatinine), and electrolytes (Na + , K + , and Cl − ) (Table 3), and the tissue morphologies of liver, kidneys, and muscle (data not shown). All these results indicated that OPH was not threaten to growing up and to the blood biochemistry of rats, and could be a safe food for its use as a long-term dietary supplement.…”
Section: Discussionmentioning
confidence: 94%
“…Okara has been reported to prevent excessive lipid absorption due to the high content of dietary fiber. 32,33 Furthermore, OPH supplementation for 4 weeks was not harmful to the serum markers of lipids (triglyceride and total cholesterol), glucose, liver (AST, ALT), kidney (uric acid and creatinine), and electrolytes (Na + , K + , and Cl − ) (Table 3), and the tissue morphologies of liver, kidneys, and muscle (data not shown). All these results indicated that OPH was not threaten to growing up and to the blood biochemistry of rats, and could be a safe food for its use as a long-term dietary supplement.…”
Section: Discussionmentioning
confidence: 94%
“…Among the various extraction methods, high temperatures can cause the degradation of these phenolic compounds, generating a loss of bioactive activity, such as antioxidant or antibiotic activities [112]. Thus, to overcome such limitations, solid-state fermentation (SSF) has been shown as an alternative method capable of producing and facilitating the extraction of these compounds from residues and the wastes from several sources of fermented foods [65,77,97]. Such fermented waste can be used as a source of carbohydrates for various microorganisms, which go through the fermentation process and generate metabolites and products that can be extracted and employed in the food industry for human health [113].…”
Section: Methods Of Obtaining Productsmentioning
confidence: 99%
“…Okara is the residual byproduct generated when processing fermented soybean food products such as miso, natto, and tempeh. Likewise, Ichikawa et al (2022) recently reported the in vivo anti-obesity effects of phenolic compounds and proteins recovered from insoluble residuals derived from okara [65]. Oliveira et al (2022) recently reported the use of yeast peptide extracts in a circular economy concept, employing membrane filtration to recover peptide fractions (48.3% proteins and 86.4% essential amino acids) [98].…”
Section: Biological Activities Functional Foods and Health Benefitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Okara is a by-product of soybean curd residue resulting from the processing of soy milk and tofu [16][17][18]. In dry matter basis, okara contains high DFs (50 %), high protein (25 %) [19][20][21], hemicellulose, phenolic content, lipid (10 %) [22], antioxidants, Isoflavones (12 to 40 %) [22,23] and vitamins [24][25][26] that are needed by the human body, particularly for the DM patients. Moreover, there is much evidence for the health benefits of DFs including hypo-glycemic activities, reducing body weight, hypo-lipidemic and anti-oxidant activities [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%